Association of Chronic Spontaneous Urticaria With Anxiety and Depression in Adolescents: A Mediation Analysis - Huang, Yuzhou; Xiao, Yi; Jing, Danrong; Li, Jie; Zhang, Jianglin; Chen, Xiang; Shen, Minxue (Frontiers in Psychiatry, 2021)
Background: Chronic spontaneous urticaria (CSU) is associated with psychiatric comorbidities. It is unknown whether the relationship is mediated by modifiable factors. Objectives: To investigate whether the effect of CSU on anxiety and depression in adolescents is mediated by the symptoms of itching and sleep disturbance. Methods: Newly enrolled college students were recruited. Skin diseases, including CSU were diagnosed by certified dermatologists during the health examination. Anxiety and depression were measured by the Generalized Anxiety Disorder Scale and Patient Health Questionnaire, respectively. Sleep quality was measured by the Pittsburgh Sleep Quality Index. The symptoms of itching was measured by the numeric rating scale. The mediation effect model was proposed according to the hypothesis and established using a structural equation model. Results: 7775 students that reported no history of systemic diseases and had no pruritic skin diseases (except CSU) were included in analysis. CSU was significantly associated with both anxiety and depression when the symptoms of itching and sleep quality were not modeled. A mediation model was proposed as CSU → itching → sleep disturbance → anxiety or depression. Itching and sleep quality mediated 65.4% and 77.6% of CSU’s effects on anxiety and depression, respectively, and CSU had no significant direct effect on anxiety or depression in the mediation models. Conclusions: The associations of CSU with anxiety and depression were mediated by the symptoms of itching and sleep disturbance.Effectively reducing the symptoms of itching thereby could increase natural sleep, which can further treat the emotional disorders among patients with CSU.